Ethnobotany of Community Food Plants on the Slopes of Merapi Merbabu, Central Java, Indonesia - Umartani, Lita Ayu; Nahdi, Maizer Said (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Ethnobotany is a study of the interaction between local communities and their natural environment, especially regarding the use of plants as food and medicinal ingredients. Food plants are a daily basic need whose existence is a necessity for the people on the slopes of Merapi Merbabu. How to use plants is transferred from generation to generation to form a culture. The research was carried out in March-May 2020 with the aim of digging public knowledge of plants used as food, including staple food, vegetables and medicines by studying the species diversity, including the benefits of organs, habit, how to use, process and how to obtain these species. The data were collected by using a combination of qualitative and quantitative methods with in-depth interviews through 40 respondents who were selected by purposive sampling. The results showed that the communities on the slopes of Merapi and Merbabu still used 74 plant species from 37 families as food plants. The favorite family is Fabaceae, followed by Zingiberaceae and Solanaceae. The most widely used hobbits’ were herbs (36.49%), followed by bush (28.38%), shrubs (18.92%) and trees (16.22%). Plant organs that are widely used are leaves (29.73%), fruit (17.57%), tubers (10.81%), seeds (9.46%), roots, rhizomes and flowers (6.76%), shoots (5.40%), stems (2.70%) and water, skin and heart (1.35%). The most common ways to use it are vegetables (29.73%), boiled (16.22%) and drunk (12.16%). How to obtain it through own cultivation (72.97%), and buying at the market (21.62). The highest use values were Adas (Foeniculum vulgare Mill.) (0.25), Lombok (Capsicum annum L.) (0.20), Kunir (Curcuma dosmetica loir) and Kangkung (Ipomoea aquatica Forsk.) (0.17). The highest importance values were Padi (Oryza sativa L.) (5.23%), and Adas (Foeniculum vulgare Mill.) (4.57%).